Management of hyperpigmentation: Current treatments and emerging therapies - Nautiyal, Avni; Wairkar, Sarika (Pigment cell and melanoma research, 2021)
Hyperpigmentation of the skin refers to a dermatological condition which alters the color of the skin, making it discolored or darkened. The treatments for hyperpigmentation disorders often take very long to show results and have poor patient compliance. The first‐line treatment for hyperpigmentation involves topical formulations of conventional agents such as hydroquinone, kojic acid, and glycolic acid followed by oral formulations of therapeutic agents such as tranexamic acid, melatonin, and cysteamine hydrochloride. The second‐line approaches include chemical peels and laser therapy given under the observation of expert professionals. However, these therapies pose certain limitations and adverse effects such as erythema, skin peeling, and drying and require long treatment duration to show visible effects. These shortcomings of the conventional treatments provided scope for further research on newer alternatives for managing hyperpigmentation. Some of these therapies include novel formulations such as solid lipid nanocarriers, liposomes, phytochemicals, platelet‐rich plasma, microneedling. This review focuses on elaborating on several hyperpigmentation disorders and their mechanisms, the current, novel and emerging treatment options for management of hyperpigmentation.